Youth empowerment for productivity: can Apprenticeship schemes turn them around? (2016)
Absence of acquisition of vocational skills on the part of the youths has been considered the bane of the economy of many African societies, particularly Nigeria. The National Directorate of Employment (NDE) schemes were the intervention strategies introduced by the government in its frantic effort to find a lasting solution to youth unemployment. In the light of the above, the study looked at the NDE schemes as a source of provider of employment through youth empowerment schemes in Oyo State, Nigeria. The descriptive research design of the expost-facto type was adopted for the study. The population for the study comprised all the youths who have benefited from the vocational skill acquisition and small scale enterprise schemes of the NDE in Oyo State, Nigeria. Random sampling technique was used to select 450 youths who benefited from the vocational skill acquisition scheme and the small scale enterprise schemes of the NDE. The instrument used was a questionnaire tagged "Skill Acquisition and Youth Empowerment Questionnaire" (SAYEQ) with four sub-sections. Two hypotheses were tested at 0.05 level of significance and the finding showed that there is significant impact of NDE vocational skill acquisition training scheme on youth empowerment (F(l.398) = 46. 769; P,<.05); there is significant impact of NDE small scale enterprises scheme on youth empowerment (F(l.398) = 99.284; P, <.05). It is recommended that industrial social worker should sensitise the government as to how best they can use these programmes (VSS and SSE) as agents of change in the life, socialisation and economic empowerment of youths within their communities and the nation at large.